Selection wages: an example - Ekkehart Schlicht (Institute for the Study of Labor (IZA), 2006)
Offering higher wages may enable firms to attract more applicants and screen them more carefully. If firms compete in this way in the labor market, selection wages emerge. This note illustrates this wage-setting mechanism. Selection wages may engender unconventional results, such as a pre-tax wage compression induced by the introduction of a progressive wage tax.
urn:nbn:de:101:1-2008050966
Keywords: 330